Pediculicidal Activity of Foeniculum vulgare Essential Oil in Treatment of Pediculus capitis as a Public Health Problem - Elham Jahanifard; Hoda Ghofleh-Maramazi; Mona Sharififard; Mohammad Mahmoodi-Sourestani; Amal Saki-Malehi; Elham Maraghi; Sima Rasaei (Journal of Arthropod-Borne Diseases, 2022)
Background: Pediculosis, caused by Pediculus spp is an important public health problem in urban and rural areas around the world. Natural compounds such as plant essential oils (EOs) have been suggested as a potential alternative for insect pest control recently. The purpose of this study was to investigate the toxicity of Foeniculum vulgare essential oil against the head louse, Pediculus capitis under laboratory conditions.